1996
DOI: 10.1200/jco.1996.14.10.2769
|View full text |Cite
|
Sign up to set email alerts
|

Combination but not single-agent methotrexate chemotherapy for gestational trophoblastic tumors increases the incidence of second tumors.

Abstract: This study suggests that there is a slight increased risk of second tumors after sequential or combination chemotherapy for GTT. This has become apparent since the introduction of etoposide and longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(64 citation statements)
references
References 17 publications
0
61
0
3
Order By: Relevance
“…This is important as it has been shown that, whilst chemotherapy regimens are highly efficacious, even the least toxic regimens used can be associated with significant sideeffects (Gillespie et al, 1997;Sharma et al, 1999) and the more rigorous regimens can be associated with long-term sequelae (Rustin et al, 1987(Rustin et al, , 1996. A stringent treatment policy does mean that definitive chemotherapy will be delayed in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as it has been shown that, whilst chemotherapy regimens are highly efficacious, even the least toxic regimens used can be associated with significant sideeffects (Gillespie et al, 1997;Sharma et al, 1999) and the more rigorous regimens can be associated with long-term sequelae (Rustin et al, 1987(Rustin et al, , 1996. A stringent treatment policy does mean that definitive chemotherapy will be delayed in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, EMA -CO causes alopecia and myelosuppression, brings forward the menopause by 3 years and increases the risk of second malignancies by approximately 1.5 fold (Rustin et al, 1996;Bower et al, 1998). As a result, many patients select MTX -FA treatment, whereas some choose EMA -CO in the belief that it is more likely to cure them rapidly.…”
mentioning
confidence: 98%
“…However, none of these studies have addressed the outcome for patients with an hCG 4100 000 IU l À1 who still score in the low-risk category. The EMA/CO regimen is associated with greater toxicity than low-risk single-agent treatment, including alopecia, myelosuppression, a reduction in the age of menopause and the increased risk of a second malignancy (Rustin et al, 1996;Bower et al, 1998). As low-risk MTX -FA conveys less toxicity, should patients with lowrisk FIGO scores but with high hCG values at least be offered this treatment initially?…”
mentioning
confidence: 99%
“…Similarly, in our series only 3 patients experienced Grade 1 acne form rash and, whereas this toxicity is not well characterized in the literature due to a lack of prospective analysis, it is our impression that it occurred less frequently and less severely than in the 5-day regimen. Also, the use of etoposide (arguably the most effective single drug to treat GTN) confers an increased risk of acute myelocytic leukemia, colon cancer, and premature menopause, 18 important issues to consider in a young, highly curable patient population.…”
Section: Discussionmentioning
confidence: 99%